(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents the migration and accumulation of chemical elements in natural and secondary saline soils, their plants, and pedobiogeochemical barriers. In addition, the biological absorption coefficient of elements in saline soil plants is presented.